76.7k views
1 vote
−2(+3)=−3(+2)+2

I am so lost

2 Answers

5 votes

Answer:

There is not solution!

Explanation:

1.

Simplify -2\times 3−2×3 to -6−6.

-6=-3\times 2+2−6=−3×2+2

2.

Simplify 3\times 23×2 to 66.

-6=-6+2−6=−6+2

3.

Simplify -6+2−6+2 to -4−4.

-6=-4−6=−4

4.

Since -6=-4−6=−4 is false, there is no solution.

User Faro
by
4.8k points
7 votes

Answer:

First you 2-+3=3+2+2 assertions is stop being dumb

Explanation:

Sdrdexvrfrfedwswdgikyf2sgikfedtjkj4whuugewef

User Jonelle
by
5.5k points